Journalism 2001 - Harper, Christopher; Indiana Group (Boulder: Course Wire Publishing, 1998)
Contents: chapter 1. storytelling. 2. finding the story. 3. researching the story. 4. computer assisted reporting. 5. the interview. 6. reporting the story. 7. covering the big story. 8. writing the story. 9. editing the written word. 10. photographing the story. 11. broadcast writing and reporting. 12. the law. 13. ethics. 14. public relations practice, writing and planning. 15. advertising. 16. reading to write. 17. resumes, cover letters, work samples and tips for getting a job. 18. the emerging world of online journalism.
Index p. 245 - 250.
Keywords: Periodismo - Prensa